2019
DOI: 10.3748/wjg.v25.i31.4502
|View full text |Cite
|
Sign up to set email alerts
|

Application of indocyanine green-enhanced near-infrared fluorescence-guided imaging in laparoscopic lateral pelvic lymph node dissection for middle-low rectal cancer

Abstract: BACKGROUND As one effective treatment for lateral pelvic lymph node (LPLN) metastasis (LPNM), laparoscopic LPLN dissection (LPND) is limited due to the complicated anatomy of the pelvic sidewall and various complications after surgery. With regard to improving the accuracy and completeness of LPND as well as safety, we tried an innovative method using indocyanine green (ICG) visualized with a near-infrared (NIR) camera system to guide the detection of LPLNs in patients with middle-low rectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 26 publications
3
54
0
1
Order By: Relevance
“…Indocyanine green (ICG) near‐infrared fluorescence imaging has shown potential for lymph node mapping in colorectal cancer, with sensitivities and specificities of 70–85 per cent 48 . Few data exist to support its use in the context of pelvic sidewall involvement of rectal cancer, but one small study 49 of 42 patients with mid‐to‐low rectal cancers found improved lymph node yield and reduced risk of incomplete LPND with concomitant use of ICG.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Indocyanine green (ICG) near‐infrared fluorescence imaging has shown potential for lymph node mapping in colorectal cancer, with sensitivities and specificities of 70–85 per cent 48 . Few data exist to support its use in the context of pelvic sidewall involvement of rectal cancer, but one small study 49 of 42 patients with mid‐to‐low rectal cancers found improved lymph node yield and reduced risk of incomplete LPND with concomitant use of ICG.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Zhou et al and Boni et al [ 56 , 57 ] showed the usefulness of ICG in harvesting pelvic lymph nodes during lateral pelvic lymph node dissection, demonstrating that the ease of localization with the help of augmented reality, especially in obese patients, allows for collection of a large number of lymph nodes (11.5 ± 5.9 vs. 7.1 ± 4.8, p = 0.017), with less blood loss (55.8 ± 37.5 mL vs. 108.0 ± 52.7 mL, p = 0.003) and over a shorter period time compared to traditional surgery [ 56 ]. In these studies, the indication of LPLD was established before surgery, not by ICG assessment of SLN on the lateral pelvic wall.…”
Section: Resultsmentioning
confidence: 99%
“…Up until now, there has been no consensus regarding the use of ICG for lymphatic mapping or SLB, but it has been proven to be useful in the assessment of the lymphatic flow in particular circumstances and it can be a helpful tool during LPLD in rectal cancer surgery. A more targeted dissection brings the benefits of minimal blood loss and reduced damage in the adjacent tissue and can shorten the learning curve for this technique [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the effective treatment methods, laparoscopic LPLN dissection (LPND) can significantly reduce the local recurrence rate compared with simple total mesorectal excision (TME) surgery. In clinical applications, LPND is limited by various complications because the ureters and hypogastric nerves might be damaged without efficient guidance, and for this using ICG improve the dissection increasing the numbers of lymph nodes harvested and decreasing complications [34].…”
Section: Evolution Of Icg In Colorectal Cancer and Literature Experiencementioning
confidence: 99%